THE EFFECT OF SOY TEMPEH FLOUR EXTRACT ON VAGINA HISTOLOGICAL STRUCTURE OF SWISS WEBSTER OVARIECTOMIZED MICE (MUS MUSCULUS) - Mahriani Mahriani; Eva Tyas Utami; Dita Ayu Faradila (UPT Penerbitan Universitas Jember, 2016)
Estrogen deficiency can changes the reproductive system especially in menopausal women, such as a decreasing of smooth muscle contraction, a thinning of vaginal structure, epithelial atrophy and a collagen decreasing. The disorders can be overcome by phytoestrogens treatment. Tempeh is a fermented soy product contains isoflavones that has estrogen-like structure with 17β-estradiol so that it can be able to bind estrogen receptors. Ovariectomized animal as animal test model has estrogen deficiency. Therefore, the purpose of this study to determine the effect of tempeh soy flour extract on vagina histological structure of Swiss Webster ovariectomized mice. The method used animals tested by treating 45 female Swiss Webster mice that were divided into five groups: negative control group (normal mice had not ovariectomized was not given tempeh flour extract), positive control (ovariectomized mice was not given tempeh flour extract), the treatment group (ovariectomized mice and was given tempeh flour extract D1 (0.21 g/ml / day), D2 (0.42 g/ml/day), and D3 (0,63 g/ml/day). Soy tempeh flour extract was given for 10, 20, and 30 days by gavage. The histological parameter were observed include tunica mucosa epithelium and tunica muscularis thickness of vagina. The result showed that tempeh flour extract increase epithelium thickness and tunica muscularis of the vagina ovariectomized mice. Treatment by taking longer time and giving higher dosage of tempeh flour extract could increase the ephitelium thickness of tunica mucosa and tunica muscularis vagina. The treatment of 0.63 g/ml/day dosage during 30 days showed the highest thickness average values of epithelium and tunica muscularis. The ephitelium thickness was 33.90 μm and the tunica muscularis dense was 90.20 μm.